Adolescents in the Gaming Zone: A Study on Depression, Anxiety, Loneliness - Shrestha, Ishika; Pun, Diparshan; Basnet, Isniya; Bhandari, Jonisha; Koirala, Karan; Mahat, Dipak (International Journal of Applied Educational Research (IJAER), 2024)
This study explored the impact of online gaming addiction on adolescents' mental health in the Kathmandu Valley. With the advent of accessible gaming platforms, there was increasing concern about their potential negative effects. Using a cross-sectional, descriptive, and causal-comparative research design, data were collected from 207 students across four colleges through structured questionnaires. The study aimed to assess adolescents' perceptions of online gaming, investigate the relationship between gaming addiction and mental health, and examine its impacts on depression, anxiety, and loneliness. The findings revealed a significant correlation between online gaming addiction and adverse mental health outcomes among adolescents. Increased gaming addiction was associated with higher levels of depression, anxiety, and loneliness. The study highlighted the detrimental effects of excessive gaming on social relationships, academic performance, and overall well-being. This research addressed a critical gap by focusing on the Kathmandu Valley, providing new insights into the localized effects of gaming addiction and underscoring the need for targeted interventions and preventive measures to support adolescent mental health.